Integrasi Model VAK dan Case Method untuk Meningkatkan Efektivitas Praktikum Jaringan Komputer - Ristanto, Riska Dami; Nashiroh, Putri Khoirin; Ekarini, Fitria (Universitas Negeri Gorontalo, 2024)
The era of disruption demands that graduates possess future skills to meet the current needs of the workforce. The urgency to train graduates with future skills lies in the development of technology and learning innovation, especially at the higher education level. The lack of integration of knowledge, skills, and attitudes, as well as differences in students' learning styles, are the main factors that affect the achievement of learning in computer networking courses. The aim of this study is to integrate the VAK (Visualization Auditory Kinesthetic) Model and Case Method to improve the effectiveness of practical learning in computer networking courses. The Research and Development (R&D) method with the Dick and Carey model approach was used in this study, which includes analysis, design, development, and testing stages. Initial identification is needed to determine the needs of students' learning styles. A field test was conducted on 60 students taking computer networking courses to determine the achievement of learning in the cognitive, skill, and attitude domains for each learning style. The results of the development of practical computer networking learning media with the integration of the VAK Model and Case Method were declared feasible based on the assessment of material experts at 96.7% and media experts at 95%. The results of the test show that this learning media can meet the learning outcomes of the computer networking course in the cognitive domain with a N-Gain value of 0.78 in the high category, as well as the skill and attitude domains with an effectiveness level of 83.2%. The application of the VAK Model and Case Method is effective in practical learning to improve students' future skills, particularly in terms of communication, collaboration, critical thinking and problem-solving across all learning styles.